2013
DOI: 10.7860/jcdr/2013/6520.3752
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Factors Affecting Low Back Pain and Safety and Efficacy of NSAIDs in Acute Low Back Pain in a Tertiary Care Hospital of Western Nepal

Abstract: Introduction: Low back pain is characterized by a range of symptoms which include pain, muscle tension or stiffness, and is localized between the shoulder blades and the folds of the buttocks, with or without spreading to the legs. Non-Steroidal Anti Inflammatory Drugs (NSAIDs) are the drugs of choice which provide an analgesic effect for acute low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…This is perhaps because the rate of current employment was also highest in Nepal which is associated with higher likelihood of experiencing back pain. A follow-up study in Western Nepal reported that LBP was higher among subjects involved in agriculture and heavy weight lifting 23. Similar evidence were reported by WHO estimates which found that ~37% of all LBP is of occupational origin 24.…”
Section: Discussionsupporting
confidence: 69%
“…This is perhaps because the rate of current employment was also highest in Nepal which is associated with higher likelihood of experiencing back pain. A follow-up study in Western Nepal reported that LBP was higher among subjects involved in agriculture and heavy weight lifting 23. Similar evidence were reported by WHO estimates which found that ~37% of all LBP is of occupational origin 24.…”
Section: Discussionsupporting
confidence: 69%
“…Being a common musculoskeletal condition, the point prevalence among the world population ranges between 60-80% 3 . The risk of LBP increases above 35 years of age, with prevalence being more among females.…”
Section: Introductionmentioning
confidence: 99%
“…Back pain is a major health problem of the world [1][2][3] about 90% adults experience back pain at some point in their lives [4], 85% never given precise pathoanatomical diagnosis [2,3,[5][6][7][8]. The incidence age is 18 -55 years.…”
mentioning
confidence: 99%
“…This includes spinal fusion and disc replacement. Medications commonly used include NSAIDs and muscle relaxants [5,10].…”
mentioning
confidence: 99%